Testing the generality of sea otter‐mediated trophic cascades in seagrass meadows. Issue 5 (2nd March 2021) - Raymond, Wendel W.; Hughes, Brent B.; Stephens, Tiffany A.; Mattson, Catherine R.; Bolwerk, Ashley T.; Eckert, Ginny L.
Abstract : The presence and strength of trophic cascades can be a function of the local abiotic environment and relative abundance of key species. The reintroduction and expansion of sea otters Enhydra lutris, a known keystone species in kelp ecosystems, in southeast Alaska provides a rare natural experiment to test the generality of a apex‐predator – seagrass trophic cascades across a broad spatial scale. We conducted an in‐depth seagrass community survey at 21 sites spanning ~100 km with variable sea otter presence to test for patterns of alternating abundance and direct relationships between species indicative of trophic cascades. Our analysis revealed some of the trophic relationships predicted by the apex predator–seagrass trophic cascades theory, including a strong negative relationship between sea otters and crabs and many of the expected relationships between nitrate, seagrass, epiphytes and epifauna. Other expected relationships within a trophic cascade, however, were not supported – including no relationship between crabs and epifauna, a critical link in the trophic cascade. Given the lack of evidence for all hypothesized direct relationships, we conclude that a sea otter mediated trophic cascade may not be present in southeast Alaska and could be due to local scale factors including the spatial heterogeneity, low resource availability and non‐linear food chains in southeast Alaska seagrass communities. However, correlation analyses suggest further interactions among biological and environmental variables in southeast Alaska seagrass communities, including a positive correlation between sea otters and seagrass biomass. These results suggest that the effects of recovering apex‐predator populations may not be generalizable across regions and spatial scales, highlighting a need for local assessment on the ecology and management of these populations.